ACTIVATED CARBONS EMPLOYED TO REMOVE IONIC LIQUIDS FROM AQUEOUS SOLUTIONS - Hassan, Safia; Ahmad, M. A.; Irfan, N.; Tufail, M.; Farooq, A.; Duclaux, L. (The Nucleus, 2011)
Imidazolium and pyridinium based ionic liquids (ILs) have been separated from aqueous solutions by adsorption using a raw Chinese activated carbon (CAC), a bleached Chinese activated carbon (BAC) and an acid treated Chinese activated carbon (AAC) as adsorbent. Adsorption isotherms data of ionic liquids on activated carbons has been obtained. The influence of both cations and anions was analyzed by studying three different ILs. The role of surface chemistry of the adsorbent was also examined using activated carbons modified by oxidative treatments. The BET surface area of activated carbons was measured by nitrogen adsorption. The results of this work indicate that activated carbon is an attractive adsorbent to remove ionic liquids from water streams. It has also been demonstrated that the adsorption of hydrophilic ionic liquids can be improved by modifying the amount and nature of oxygen groups on the activated carbon surface specially by increasing basic groups. The adsorption data for isotherms was studied at acidic, neutral and basic pH values.